"What does skateboarding mean to you?" An exploratory study of Brazilian skateboarders` developmental experiences - Costa, G. H.; Kochanek, J.; Erickson, K. (Qualitative Research in Sport, Exercise and Health, 2023)
Despite the widely held belief that participation in organised sport promotes Positive Youth Development (PYD), the evidence supporting this notion remains limited. Alternatively, scholars have investigated the potential for action sports to contribute to young people`s development. In particular, skateboarding may represent a more accessible and inclusive option compared to traditional sports as evidenced by its increasing popularity amongst youth in Brazil and worldwide. While the potential to promote positive development warrants attention, as development through sport should be an option for all, it is particularly important to understand the experiences of historically marginalised groups such as women. The purpose of the current study was to (a) explore the developmental experiences afforded by skateboarding, and (b) women`s unique experiences within this setting. Reflexive thematic analysis was employed to analyse Brazilian skateboarders semi-structured interviews and responses to a commensurate open-ended survey. Taken together, results suggest skateboarders were able to develop both individual (e.g. resilience) and collective-level outcomes (e.g. social capital) due to this sport`s peer-centred, self-structured, and community-oriented nature. While female skateboarders were faced with a consistent set of gender-related constraints, they employed both individual and collective strategies to navigate these constraints and empower women within this setting. Overall, skateboarding provided different developmental experiences and outcomes when compared to traditional sports. The nature of skateboarding encouraged participants to reflect on and engage in sociopolitical processes (e.g. protesting), empowering this group of young people and situating them as capable of enacting social change within their communities.